Health in the Era of the Internet of Things: A Domain-Specific Modelling Language - Strobel, Gero (Proceedings of the 54th Hawaii International Conference on System Sciences (HICSS), 2021)
Based on the cultural, social and technological development of the last hundred years, the pursuit of health driven by primal instincts has been transformed in most areas worldwide into a quasi de facto standard. But this security is deceptive. Not only the global developments of the last few months, but also creeping factors such as demographic change or the steadily growing world population are putting increasing pressure on the healthcare system. Today, more and more health care systems based on continuous demand for medical resources are increasingly reaching their limits. Technologies such as the Internet of Things are not a panacea, but offer great potential for increasing the flexibility and efficiency of healthcare systems. However, the development of such IoT-based healthcare systems requires a holistic understanding of the information technology as well as the domain itself. Against this background, the paper presents a domain-specific modelling language for IoT-based healthcare systems
Keywords: Smart Health; Internet of Things; Domain Specific Modelling Language